Inhibitory effects of caraway (Carum carvi L.) and its component on N-methyl-N'-nitro-N-nitrosoguanidine-induced mutagenicity - Masanori Mazaki (2018)
To elucidate the mechanism of antimutagenicity of caraway, we examined the effects of caraway seed extract on N-methyl-N'-nitro-N-nitrosoguanidine (MNNG)-induced mutagenesis in DNA methyltransferase-deficient Salmonella typhimurium strains, O6-methylguanine DNA adduct formation, and thiol content in S. typhimurium cells. MNNG was highly mutagenic for ogt-strains YG7104 (ogt-ada+) and YG7108 (ogt-ada-), and it showed slightly higher mutagenicity in strain YG7100 (ogt+ada-) than in strains TA100 and TA1535. Hot water extract of caraway seeds inhibited MNNG-induced mutation only in the ogt+strains. In the presence of caraway extract, O6- methylguanine DNA adducts in strain YG7100 were decreased in proportion to the decrease of MNNG-induced mutagenesis. Although MNNG is known to degrade in the presence of thiols to produce methyl cation which can react with DNA, caraway had no effect on cellular concentrations of acid-soluble thiols. These results indicate that caraway does not directly inactivate MNNG and that Ogt-O6-methylguanine-DNA methyltransferase may be involved in the antimutagenic activity of caraway.